Optimization of ready-to-drink turmeric-ginger-lemongrass infused citrus juice blend - Sayson, Stewart Vincent R.; Villarino, Casiana Blanca J. (Quezon City College of Home Economics, University of the Philippines Diliman, 2017)
The study aimed to optimize the formulation for a ready-to-drink citrus juice blend infused with lemongrass, turmeric, and ginger through response surface methodology (RSM) with a central composite rotatable design. Models were generated to evaluate the effects of formulation parameters on the pH, total soluble solids, and acceptability of the product. The amounts of each ingredient were optimized to produce juice blends with desirable physico-chemical properties with acceptable sensory characteristics. Verification experiments were performed to assess the predictive capacity of the models. The models generated showed significant third-order effects on pH and TSS (p<0.05). In general, acceptability was affected by interactions of the ingredients. Furthermore, color acceptability followed a quadratic model. Optimization has shown that using a combination of 554.47- 819.61g lemongrass, 89.36 - 106.81g turmeric, and 25.00 - 42.90g ginger can produce a juice blend with desirable physico-chemical properties and acceptable sensory characteristics. Verification runs also showed that the models accurately predicted the responses. This study revealed that lemongrass, turmeric, and ginger can be successfully infused into a beverage highly acceptable for consumers.
Thesis Classification: P
Thesis (B.S. Food Technology)--University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: Citrus juices